Efforts to Improve High School Students' Table Tennis Skills Using Interval Training Methods - Sarjono Sarjono; Budi Setiawan (Asosiasi Profesi Multimedia Indonesia, 2023)
The goal of this classroom action study was to help students in class XI IPA 4 semester 2 at SMA Negeri 3 Sukoharjo in the 2021/2022 academic year enhance their table tennis playing skills through the use of interval training. Students in the second semester of class XI IPA 4 in the 2021/2022 academic year will serve as participants in this action research in the classroom. The source of the data came from observations of table tennis training activities through the interval training method. Observational approaches, test forms, questionnaires, and point documentation were employed for data gathering. Data analysis techniques used cycle points consisting of two cycles with steps including planning, evaluation and reflection. The results showed that the interval training method in the game of table tennis carried out by the researcher showed the results of cycle 1: students' skills were in the moderate category 11 students, 14 students were lacking and 7 students were not very low. Cycle 2 results: showed student skills in the security guard category 13 students, category good 11 students and very good category 8 students. This is evident from the results of research conducted in two cycles, namely the results of hitting students right on target that have been determined to have increased from the test results cycle I with the results of the test cycle II.